Molecular basis of converting proteases to ligases - Chang, Hong Yi (Nanyang Technological University, 2020)
Peptide asparaginyl ligases (PALs) are an unusual subgroup of asparaginyl endopeptidases (AEPs). They share the same protein structure but catalyse different reactions. AEPs hydrolyse the Asx (Asn/Asp)-Xaa bond while PALs ligate them. PALs are the processing enzymes that mediate the backbone cyclization of plant cyclic peptides, such as cyclotides. Thus, much research has been conducted to explore factors that enable PALs to catalyse such naturally rare reactions. To date, residues in two areas near the active site are proposed to dictate ligation activity and have been named ligase-activity determinants (LADs). In this study, we aim to validate the concept of LADs by using a consensus plant AEP (cAEP) sequence. Four variants of the consensus sequence designated as cAEP(-/-), (+/+), (+/-) and (-/+), were designed where the two LADs sites either correspond to AEPs, PALs or chimera of both, respectively. The variants were recombinantly expressed in bacteria and purified for activity characterisation. Results show that cAEP(-/-) displayed AEP-like pH-dependent activity. By changing two residues, cAEP(+/+) displayed PAL-like ligase activity. In summary, the catalytic reaction governed by LADs has been validated using consensus plant AEP sequences which can be used for the discovery of PALs and the engineering of AEPs to PALs.